Kepuasan Pasien Terhadap Layanan Makanan Rumah Sakit - Emira Trisilawati (Nur Science Institute, 2021)
Background: Food service has become an important issue in hospital settings, as patients in recovery require a balanced diet in addition to medical supplies and care. Patient satisfaction on the quality of nutritional services affects the image of the hospital and has implications for increasing hospital income. The challenges faced by hospital food services are multi-faceted due to the varying dietary needs of patients. Hospitals are expected to be able to meet patient satisfaction related to food service needs in the midst of these multi-faceted challenges. Objective: The purpose of writing this article is to examine the factors related to patient satisfaction with hospital food services. Methods: This writing uses the literature review method. The criteria for articles used as references are articles published for the past 5 years, between 2016-2021. The analysis used in this research is content analysis. Conclusion: Patient satisfaction with food services in hospitals is influenced by several factors, including: food quality, staff/service problems, food presentation, physical environment, hunger factors and food quantity, and food delivery (distribution)